Clinical Significance of Auditive Involvement in Rheumatoid Arthritis: A Case-Control Study. (15th February 2011) - Alonso, Laura; Gutierrez-Farfan, Ileana; Peña-Ayala, Angelica; Perez-Bastidas, Maria-Esther; Espinosa, Rolando
Abstract : Introduction . Rheumatoid arthritis (RA) can involve the incudomalleolar or incudostapedial articulations. Objective . To know the punctual prevalence of audiological alterations in patients with RA. Patients and Methods . RA patients and their controls (Cs), were evaluated by Tonal Audiometry (AU); if there were alterations in the air conduction (AC), bone conduction (BC), Logoaudiometry (LG), and Tympanometry (T) were performed. Results . 45 RA patients and 45 Cs were evaluated. RA patients had 40% of bilateral and 17.8% unilateral alteration versus Cs with 22.2% bilateral and 4.4% unilateral alteration versus Cs with 22.2% bilateral and 4.4% unilateral in AC audiometry. In conventional T (CT) As-type curves in patients with RA, there were 22 LE (48.8%) and 26 RE (57.7%) versus Cs, there were16 RE (35.5%) and 20 LE (44.4%). In High-frequency T (HFT): the 3B1G pattern in RA more frequent versus Controls (Cs) in RE (P = .002 and LE (P = .01 ). There were no differences according to RA activity or RA disease evolution. Conclusions . There is a greater tendency of auditive loss of As curves in CT (rigidity in ossicular chain) and of the 3B1G pattern in HFT in RA.